Distortion of maternal-fetal angiotensin II type 1 receptor allele transmission in pre-eclampsia. Issue 8 (August 1998) - Morgan, L; Crawshaw, S; Baker, P N; Brookfield, J F; Broughton Pipkin, F; Kalsheker, N
Abstract : OBJECTIVE: To investigate the fetal angiotensin II type 1 receptor genotype in pre-eclampsia. DESIGN: Case-control study. POPULATION: Forty-one maternal-fetal pairs from pre-eclamptic pregnancies and 80 maternal-fetal pairs from normotensive pregnancies. METHODS: Maternal and fetal DNA was genotyped at three diallelic polymorphisms, at nucleotides 573, 1062, and 1166, in the coding exon of the angiotensin II type 1 receptor gene, and at a dinucleotide repeat polymorphism in its 3' flanking region. RESULTS: Allele and genotype frequencies at the four polymorphic regions investigated did not differ between pre-eclamptic and normotensive groups, in either fetal or maternal samples. Mothers heterozygous for the dinucleotide repeat allele designated A4 transmitted this allele to the fetus in 15 of 18 informative pre-eclamptic pregnancies and in eight of 26 normotensive pregnancies. This was greater than the expected probability in pre-eclamptic pregnancies (p=0.04) and less than expected in normotensive pregnancies (p<0.005). The 573T variant, which is in partial linkage disequilibrium with the A4 allele, showed a similar distortion of maternal-fetal transmission. CONCLUSION: Angiotensin II type 1 receptor gene expression in the fetus may contribute to the aetiology of pre-eclampsia. It is unclear whether susceptibility is conferred by the fetal genotype acting alone, or by allele sharing by mother and fetus. Possible mechanisms for the effect of the angiotensin II type 1 receptor gene are suggested by the association of the 573T variant with low levels of surface receptor expression on platelets. If receptor expression is similarly genetically determined in the placenta, responsiveness to angiotensin II may be affected, with the potential to influence placentation or placental prostaglandin secretion.